A photoacoustic-surface-acoustic-wave sensor for ring-stage malaria parasite detection - Wang, Shaomeng (2022)
The detection of malaria parasite (plasmodium falciparum) is investigated by using a novel photoacoustics (PA) excited surface acoustic wave (SAW) sensor. The SAW sensor is designed to resonant around 10 MHz and is fabricated by using standard two-step photolithography. The photoacoustic PA-SAW sensing system is composed of a SAW sensor, cooperating with a pulsed laser, a neutral density filter, a convex lens, two analog front ends (AFEs) and an oscilloscope. PA signals and their spectrums of different materials are obtained for calibration, and the PA signals of normal blood and infected blood are chaterized through the PA-SAW sensing system, subsequently. The infected blood with cultured ring-stage malaria parasites concentrations of 1% can be detected. The demonstration shows that the PA-SAW sensor has good potential in the diagnosis of malaria at early stage.